Princesses and paupers: a content analysis of socioeconomic status in animated Disney films. Issue 3 (3rd July 2022) - Shawcroft, Jane E.; Coyne, Sarah M.; Brubaker, Pamela Jo; Zurcher, Jessica D.
ABSTRACT: This paper examines depictions of SES in Disney animated films to learn about the stereotypes of different socioeconomic status (SES) groups that these films reinforce or dispel. As Disney films are frequently watched by children, and may have important developmental implications for the internalization of stereotypes. Sixty-one animated Disney films were coded f (323 characters). Characters were coded for their SES and various roles and behaviors. Results suggest low SES characters are underrepresented compared to the US population, and that Disney's portrayal of SES both reinforces and contradicts stereotypes. IMPACT SUMMARY: Prior State of Knowledge: Socioeconomic status is a significant factor in children's development. As Disney media is often watched by children, the stereotypes of SES in Disney films are important to understand. Novel Contributions: Overall, this research indicates that low SES characters are underrepresented compared to the general US population and are more often racial minorities than mid and high SES characters. Few other characteristics examined, however, were significantly different based on SES. Practical Implications: Parents should be aware of and discuss the racial differences in socioeconomic status in Disney films with children. Furthermore, future research should examine the effect of depictions of socioeconomic status in children's media on children's stereotypes.